(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
In this article, the integration of automated asynchronous electrical circuit block circuit devices and blocks into a single microprocessor system is highlighted, as well as increasing the functionality and speed of the electric circuit, it also leads to structural compactness.